Local Government Preparedness in Response to the Transition from Pandemic to Endemic: An Adaptive Governance Perspective in Surabaya Municipality - Suhartono Winoto; M.R Khairul Muluk; Lestari Eko Wahyudi (Universitas Sultan Ageng Tirtayasa, 2023)
According to the declaration of the WHO about the pandemic, COVID-19 is pathogenic in humans. Leaders around the world have implemented strategies to prevent the transmission of this outbreak. The Indonesian government also encountered a similar problem, with the first case of COVID-19 in Indonesia announced around March 2020. Soon after, the number of cases increased dramatically over time. Months later, the Indonesian government distributed the vaccination program throughout the country, reaching more than 70% of the population. As the immune system strengthens, the government is planning a transition from pandemic to endemic based on the condition of each area. Adaptive governance is needed during this transition, and according to that, the local government plays an important role in dealing with the endemic. Further research has been conducted in Surabaya, one of the largest cities in Indonesia with a heterogeneous population. This study used Soft System Methodology to create a model of bureaucracy between local governments in Surabaya, and the results showed that in the relationship between local governments, the mayor of Surabaya Municipality has to be the main commander, with the regional disaster management agency as the leading sector. However, the results showed that adaptive governance in Surabaya has been effectively implemented. This study is expected to be one of the references in preparing for the transition from pandemic to endemic by using an adaptive governance perspective.